UJI KINERJA ALAT KONTROL KEKERUHAN DAN DERAJAT KEASAMAN UNTUK PENYEDIAAN AIR BAKU TANAMAN HIDROPONIK BERBASIS MIKROKONTROLER ARDUINO UNO R3 - Prima, Fidel Harmanda (Jurnal Technopreneur (JTech), 2024)
This research aimed to test the performance of turbidity and pH control devices using turbidity sensors and microcontroller-based pH sensors. This research was conducted from November 2017 to July 2018 at the Energy & Electrification Laboratory and Workshop of the Department of Agricultural Technology, Faculty of Agriculture, Sriwijaya University, Indralaya. The method used was experimental method with the presentation of results using descriptive data in the form of tables and graphs. The parameters observed were structural and functional design, flow rate, power requirements, accuracy and precision. Each parameter was repeated 4 times. The power required by the microcontroller device and sensors in operation is 4.04 W, the power requirement for four selenoids when working is 49.92 W and the power requirement for two DC pumps when working is 66.56 W. The average time for filling water to full storage is 16.84 minutes and the volume of water is 70 L, so the water discharge obtained from the calculation of volume per time is 4.16 L/min. Testing the accuracy and precision of turbidity sensors and pH sensors aims to determine the percentage of the actual value, the average value of pH sensor accuracy is 95.28% with an average value of sensor precision of 98.48% and the average value of turbidity sensor accuracy is 78.60% with an average value of sensor precision of 92.74%.